Effect of Maltodextrin Substitution on Physicochemical and Sensorial Properties of Malay Traditional Cake ‘Bahulu’ - Afifah Mohd Junaidishah, Nur; Bujang, Aishah (International Journal of Engineering and Technology, 2019)
Although Malaysia is not a wheat-producing country, most Malaysian traditional foods uses wheat flour as its main ingredient. One ingredient substitution for wheat flour is modified starch, maltodextrin. The aim of this study was to assess the effects of wheat flour substitution with maltodextrin on physicochemical and sensorial properties of a Malay traditional cake, â€˜bahuluâ€™. Changes in the viscosity of batter, water activity (aw), specific volume, colour, texture profile and sensorial preference of â€˜bahuluâ€™ with 5% (M5), 10% (M10) and 15% (M15) maltodextrin substitution were measured. The results showed that with increase substitution of maltodextrin, batter viscosity, specific volume and aw values decreased. However, redness (+a*) of crust and yellowness (+b*) of crust and crumb, hardness, springiness, gumminess and chewiness of â€˜bahuluâ€™ increased. No significant difference was observed for L* (lightness) and â€“a* (greenness) of crumb, adhesiveness and cohesiveness. Compared to control, â€˜bahuluâ€™ with maltodextrin substitution showed reduction in degree of preference for sensory score except for texture attribute. This study indicates that replacement of wheat flour is possible at a certain level of substitution, Â however, further improvements are required in order to maintain the quality of the Malaysian heritage food.Â Â Â